Assessing the Readiness for 15-Minute Cities: Spatial Analysis of Accessibility and Urban Sprawl in Limassol, Cyprus - Nikolaou, Paraskevas; Basbas, Socrates; Ioannou, Byron (My University, 2025)
This study evaluates Limassol’s readiness to adopt the 15-minute city model through a spatial accessibility and urban-form analysis. Using openly available geo-referenced Points of Interest (POIs), road network data, land-use records, and census information, we generated 15-minute walking and cycling isochrones for eight essential urban functions: Education, Food, Green Areas, Health, Services, Shopping, Tourism, and Transport. Residential coverage within each isochrone was calculated to assess accessibility equity across the city. Urban sprawl was quantified using size, density, and fragmentation metrics derived from historical planning zones. Results show that while cycling accessibility is high for most categories (85–95% of residential areas), walking accessibility is considerably lower and unevenly distributed, with several critical functions, particularly Green Areas, Education, and Transport, serving less than half of the residential zones. The analysis also reveals increasing spatial fragmentation and outward population shifts consistent with low-density sprawl, driven by planning policies and development pressures. These findings indicate that Limassol is only partially aligned with the principles of the 15-minute city, with significant gaps in walkable access and decentralized service provision. The study concludes that targeted planning reforms, improved active-mobility infrastructure, and polycentric redistribution of amenities are necessary for enhancing accessibility equity and advancing the city’s transition toward a more sustainable and human-scaled urban model.
Keywords: points of interest; sustainable development; 15-minute city; urban sprawl; spatial accessibility; urban planning; isochrones